CHARACTER EDUCATION IN KH. BISRI MUSTOFA’S NGUDI SUSILA; IMPLICATIONS FOR MILLENNIAL STUDENTS - Fariq Qoirul Fuadi (Pascasarjana Universitas Wahid hasyim Semarang, 2025)
In the millennial era, students now seek knowledge, understanding and references about religion on social media by ignoring the role of teachers and book references, because it is too easy to gain religious knowledge on social media without the help of experts. There is a need to instill in students to create a charismatic character by re-exploring the teachings from classical books which have been proven so far to be able to make students, especially among students, have better behavior, one of which is through teaching the value of ayng tengdung in the Poetry in the Book. Ngudi Susila Chapter Ing Pamulangan has language and form that is easy for millennial students to understand, so that the character formation of millennial students will be easily accepted and in the next process the values contained in the book will be implemented by students.This type of research is qualitative with a literary approach with the primary source being the Book of Ngudi Susila by KH. Bisri Mustofa, and data collection techniques through historical methods, library research methods and descriptive methods, the data that has been obtained is then analyzed using Content Analysis, deductive methods and reflective thinking methodsThe results of the study show: 1) Learning problems among millennial students arise because they believe in interactive information more than unidirectional information, they prefer cellphones, millennials are required to have social media, millennials are more likely to behave pragmatically and instantaneously, while learning is more about concentrating on increasing intelligence and not towards increasing students' morals so that it is easy plunged into moral decadence. 2) The concept of character education in the Book of Ngudi Susila Bab Ing Pamulangan by KH. Bisri Mustofa is embodied in the form of a pegon Arabic poem which teaches students about the discipline of learning readiness and returning to school, learning ethics for students and parents, qona'ah, attention and being active in learning, good friends and reverence for teachers. 3) Implications of KH. Bisri Mustofa in the Ngudi Susila book Chapter Ing Pamulangan on character education in modern education lies in his teachings which emphasize morality by building akhlakul karimah by emphasizing on instilling the discipline of readiness to learn and return to study, learning ethics for students and parents, qona'ah, attention and active in learning, make good friends and respect teachers so that later it will have an impact on the formation of the character of modern students to develop their knowledge on an intellectual and moral basis, so that character education is not only the transfer of knowledge, but what is important is the transfer of values that prioritizes morality karimah, so that the moral decadence that is rife in the character of modern students can be reduced and build the personality of modern students into individuals with good character which ultimately builds an ethical societyKeywords: Character Education, KH. Bisri Mustofa, Book of Ngudi Susila